2014
DOI: 10.1590/s1677-5538.ibju.2014.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Robotic repair of vesicovaginal fistulae with the transperitoneal-transvaginal approach: A case series

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Objective: To describe a novel technique of repairing the VVF using the transperitoneal-transvaginal approach. Materials and Methods:From June 2011 to October 2013, four patients with symptoms of urine leakage in the vagina underwent robotic repair of VVF with the transperitoneal-transvaginal approach. Cystoscopy revealed the fistula opening on the bladder. A ureteral stent was placed through the fistulous tract. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Vesicovaginal fistulae (VVF) represent a significant morbidity in female urology with an incidence that varies between 0.3 and 2%, most of which are iatrogenic [1]. It is estimated that 0.8 per 1000 of all hysterectomies are complicated by the development of a VVF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicovaginal fistulae (VVF) represent a significant morbidity in female urology with an incidence that varies between 0.3 and 2%, most of which are iatrogenic [1]. It is estimated that 0.8 per 1000 of all hysterectomies are complicated by the development of a VVF.…”
Section: Introductionmentioning
confidence: 99%
“…The success of VVF repair depends on various factors, including fistulae size, location, timing from the antecedent event, severity, quality of surrounding tissue, clinical experience, and surgical skill [1]. Surgical repairs of VVF are most commonly performed: (1) vaginally, (2) abdominally, and (3) laparoscopically.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their results, the authors summarized that extravesical VVF repair has similar cure rates compared to the traditional transvesical approach [ 144 ]. Most recent technology used in the treatment of VVF repair is the robotic-assisted approach and some authors reported excellent results with this operation technique [ 23 , 30 , 58 , 98 ]. Disadvantages include increased learning curve, time, costs and surgeons experience.…”
Section: Discussionmentioning
confidence: 99%
“…The mean operative time in the literature ranges from 110 to 330 minutes even in cases of robot-assisted laparoscopic repair cases. 4 The operative time in our case was 65 min. Intraoperative difficulties were noted in the first case, which included grasping the fistula, pressure of insufflation to maintain the pneumovesicum during port insertion.…”
Section: Discussionmentioning
confidence: 59%